TINCTORIS AND SIGNA CONGRUENTIAE: A NEW PERSPECTIVE. (October 2019) - Whittaker, Adam
Abstract : The notational treatises of Johannes Tinctoris are among the most important texts on late fifteenth-century musical practice. His monumental treatise on the art of counterpoint, De arte contrapuncti, affords modern scholars a great insight into the intricacies of counterpoint practice on the cusp of the era of printed music theory. In the examples for this text, Tinctoris regularly uses additional markers to specify the key passages he is discussing. These signs often closely resemble signa congruentiae, though their function in these theoretical contexts is somewhat different from the deployment of such symbols in practical music sources. This article re-examines the historical justification for the term signa congruentiae, offering a new perspective on Tinctoris's usage of such signs to explicate the rich text–example relationship underpinning his theoretical arguments and drawing attention to some novel uses of these signs that underpin these relationships.